Programming Multifaceted Pulmonary T Cell Immunity by Combination Adjuvants - Chandranaik B. Marinaik; Brock Kingstad-Bakke; Woojong Lee; Masato Hatta; Michelle Sonsalla; Autumn Larsen; Brandon Neldner; David J. Gasper; Ross M. Kedl; Yoshihiro Kawaoka; M. Suresh (Cell Reports Medicine, 2020)
Summary: Induction of protective mucosal T cell memory remains a formidable challenge to vaccinologists. Using a combination adjuvant strategy that elicits potent CD8 and CD4 T cell responses, we define the tenets of vaccine-induced pulmonary T cell immunity. An acrylic-acid-based adjuvant (ADJ), in combination with Toll-like receptor (TLR) agonists glucopyranosyl lipid adjuvant (GLA) or CpG, promotes mucosal imprinting but engages distinct transcription programs to drive different degrees of terminal differentiation and disparate polarization of TH1/TC1/TH17/TC17 effector/memory T cells. Combination of ADJ with GLA, but not CpG, dampens T cell receptor (TCR) signaling, mitigates terminal differentiation of effectors, and enhances the development of CD4 and CD8 TRM cells that protect against H1N1 and H5N1 influenza viruses. Mechanistically, vaccine-elicited CD4 T cells play a vital role in optimal programming of CD8 TRM and viral control. Taken together, these findings provide further insights into vaccine-induced multifaceted mucosal T cell immunity with implications in the development of vaccines against respiratorypathogens, including influenza virus and SARS-CoV-2.